2017
DOI: 10.1111/gfs.12288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compaction, delayed sealing and aerobic exposure on maize silage quality and on formation of volatile organic compounds

Abstract: Physical and management factors, such as compaction and sealing, greatly influence the outcome of forage conservation. This study aimed to determine the effects of compaction, delayed sealing and aerobic exposure after ensiling on maize silage quality and on formation of volatile organic compounds. Whole‐crop maize (277 g/kg dry matter [DM]) in 120‐L plastic silos was compacted at either high or low density, and sealed immediately or with delay at 2 days or 4 days post‐filling (six replicates each). After ensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 33 publications
4
29
1
7
Order By: Relevance
“…Silage subsamples (50 g) were used to analyse the fermentation pattern which is described in detail in Brüning et al. (). Briefly, the following procedures and measurements were conducted: cold‐water extracts were prepared by blending the frozen samples with 200 ml distilled water and 1 ml toluene and refrigerated overnight (4°C) afterwards filtered (Minisart RC, 0.45 μm pore size, Sartorius, Göttingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Silage subsamples (50 g) were used to analyse the fermentation pattern which is described in detail in Brüning et al. (). Briefly, the following procedures and measurements were conducted: cold‐water extracts were prepared by blending the frozen samples with 200 ml distilled water and 1 ml toluene and refrigerated overnight (4°C) afterwards filtered (Minisart RC, 0.45 μm pore size, Sartorius, Göttingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For consideration of possible variance heterogeneity, two different approaches were evaluated as described by Brüning et al. (). ANOVA was performed with the SAS MIXED procedure using the restricted maximum‐likelihood algorithm (Schabenberger & Pierce, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In developed countries, nitrogen oxide (NO x ) emissions from fertilizer and manure accounted for 27% of GHG emissions and CO 2 from all farm sources accounted for 21% of GHG emissions. Weiss, Kroschewski, and Auerbach (2016) and Brüning, Gerlach, Weiss, and Südekum (2018) found that elevated concentrations of VOC were associated with delayed silo sealing which was accompanied by increased ethanol and yeast counts. Differences in methods of crop storage did not appear to be specifically addressed in that analysis.…”
Section: Global Warmingmentioning
confidence: 99%